States and transnational corporations: a strategic alliance in extractivism - Patricia Agosto (Revista Kavilando, 2017)
The destiny that the states have defined for Our America is the recreation of the role of suppliers of raw materials that has marked our history since the conquest and colonization. The extractivism marks the rhythms of the economies, the societies, the state policies, the relations with the nature and determines a differentiated role, hierarchically inferior, in the relations with the countries of the north. The states at all levels create the necessary conditions for extractive companies, most of them transnational, to deploy their investments and develop their mega enterprises, prioritizing those interests before the rights of populations and nature. It is a strategic alliance between states and corporations that has provoked multiple resistance in the populations of the territories "sacrifices" to extractivism, as well as numerous voices that from the different critical thought / action strands pose ways to build alternatives to this model of "Development" which, in its eagerness to achieve supposed progress for our countries, does nothing but deepen the commodification of life and territories.